Exceptional bloom of toxic cyanobacteria on the Uruguayan coast, summer 2019 (INNOTEC, 2019)
Cyanobacterial toxic blooms are a worldwide problem. In Rio de la Plata basin, anthropic eutrophication and dam construction have promoted an increase in cyanobacteria blooms, especially those of the Microcystis aeruginosa complex (CMA). Here, we describe the exceptional blooms observed in the summer of 2019 on the coast of Río de la Plata and Atlantic coast of Uruguay. We discuss the main driving mechanisms using biological, meteorological and oceanographic sampling data, satellite images and reanalysis. The blooms covered a wide surface (Carmelo to Rocha; 500 km) and were persistent in time (ca. 4 months). Blooms were generated by CMA organisms having similar genetic structure and were associated to quantifiable and high microcystin concentrations. Given the observed oceanographic conditions and the similarity in organisms traits, we hypothesized that blooms had a common origin, probably associated with zones with high nutrient concentrations and high water residence time in the lower Rio de la Plata basin. Extreme precipitations induced high water flows that transported cyanobacteria blooms downstream. In addition, anomalous wind and temperature conditions facilitated their arrival to the Atlantic coast along Rocha, to environments with particular relevance for biodiversity and conservation (e.g. Rocha coastal lagoon).
Keywords: Microcystis aeruginosa commplex; summer 2019; microcystins; mcyJ gene; precipitation and water discharge extremes